2003
DOI: 10.1080/1478641031000062214
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Determination of a Novel Furanic Ester from the Aerial Part of Prasium Majus

Abstract: The aerial part of Prasium majus provided a new furanic ester, 2-2-[(5-formyl-6[(5-formylfuran-2-yl)methoxy] succinic acid dimethyl ester, (+/-)-hiziprafuran. Its structure was principally established by one- and two-dimensional NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Comparison of the 1 H NMR data of 1a with those of melittoside nonaacetate previously isolated from P. majus [2][3][4][5][6]9] (table 1) showed great similarity with the only notable exception being that, the signals from the methylene protons borne by C 10 were shifted upfield to 4.25 ppm (H 10a ) and 4.33 ppm (H 10b ). Moreover, in the 13 C NMR spectrum, most of the signals were very similar to those of melittoside nonaacetate except those assigned to C 7 (Á 19 ppm) and C 8 (Á 15.9 ppm) (table 1).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Comparison of the 1 H NMR data of 1a with those of melittoside nonaacetate previously isolated from P. majus [2][3][4][5][6]9] (table 1) showed great similarity with the only notable exception being that, the signals from the methylene protons borne by C 10 were shifted upfield to 4.25 ppm (H 10a ) and 4.33 ppm (H 10b ). Moreover, in the 13 C NMR spectrum, most of the signals were very similar to those of melittoside nonaacetate except those assigned to C 7 (Á 19 ppm) and C 8 (Á 15.9 ppm) (table 1).…”
Section: Resultsmentioning
confidence: 77%
“…Our studies of the plant Prasium majus (Lamiaciatae) known in Greek folk medicine as a tranquilizer [1] have afforded chrysoeriol glycoside, melittoside [2], 3-O--D-glycopyranosyl sitosterol, ergosterol peroxide [3], 4 0 -hydroxy-3 0 -methoxyphenyl methylcetone [4] and a new furanic ester hiziprafuran [5]. During the course of these continuing investigations, the acetylated methanol extract of the aerial parts of this plant was subjected to silica gel column chromatography, crystallisation and semi preparative HPLC which led to isolation of a new iridoid glycoside hamighriprasin as its nonaacetate 1a, the previously reported myoporoside as its pentaacetate 2a [6], -D-glycopyranose pentaacetate 3a [7] together with the saccharose octaacetate 4a [8].…”
Section: Introductionmentioning
confidence: 99%
“…Boukamcha et al 6 reported that P. majus has been used as a tranquillizer. Little is known about the chemistry of P. majus.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the chemistry of P. majus. Bouazizi et al 7 reported the isolation of a phenolic derivative and Boukamcha et al 6 the isolation of a furanic ester, hiziprafuran. To the best of our knowledge, this is the first report on the essential oil composition of P. majus.…”
Section: Introductionmentioning
confidence: 99%
“…Some non-volatile products have been isolated and identified in the plant [10,14,15]. Recently the essential oil composition of plants from Greece was reported [16].…”
mentioning
confidence: 99%